Monopsony Exploitation in Professional Sport: Evidence from Major League Baseball Position Players, 2000–2011. (15th June 2016) - Humphreys, Brad R.; Pyun, Hyunwoong
Abstract : Some professional athletes still face monopsony power in labor markets, underscoring the importance of estimating players' marginal revenue product to assess its effects. We introduce two new empirical approaches, spline revenue functions and fixed‐effects stochastic production functions, into the standard Scully (1974) approach to marginal revenue product estimation and calculate Monopsony Exploitation Ratios (MERs) for position players in Major League Baseball over the 2001–2011 seasons. Estimates indicate that MERs are about 0.89 for rookie players, 0.75 for arbitration eligible players, and 0.21 for free agents. Recent collective bargaining agreements have reduced MERs for free agents, but had no effect on MERs for other players. Copyright © 2016 John Wiley & Sons, Ltd.